In vivo monitoring of intracellular Ca2+ dynamics in the pancreatic β-cells of zebrafish embryos. Issue 6 (2nd November 2018) - Lorincz, Reka; Emfinger, Christopher H.; Walcher, Andrea; Giolai, Michael; Krautgasser, Claudia; Remedi, Maria S.; Nichols, Colin G.; Meyer, Dirk
ABSTRACT: Assessing the response of pancreatic islet cells to glucose stimulation is important for understanding β-cell function. Zebrafish are a promising model for studies of metabolism in general, including stimulus-secretion coupling in the pancreas. We used transgenic zebrafish embryos expressing a genetically-encoded Ca 2+ sensor in pancreatic β-cells to monitor a key step in glucose induced insulin secretion; the elevations of intracellular [Ca 2+ ]i . In vivo and ex vivo analyses of [Ca 2+ ]i demonstrate that β-cell responsiveness to glucose is well established in late embryogenesis and that embryonic β-cells also respond to free fatty acid and amino acid challenges. In vivo imaging of whole embryos further shows that indirect glucose administration, for example by yolk injection, results in a slow and asynchronous induction of β-cell [Ca 2+ ]i responses, while intravenous glucose injections cause immediate and islet-wide synchronized [Ca 2+ ]i fluctuations. Finally, we demonstrate that embryos with disrupted mutation of the CaV 1.2 channel gene cacna1c are hyperglycemic and that this phenotype is associated with glucose-independent [Ca 2+ ]i fluctuation in β-cells. The data reveal a novel central role of cacna1c in β-cell specific stimulus-secretion coupling in zebrafish and demonstrate that the novel approach we propose – to monitor the [Ca 2+ ]i dynamics in embryonic β-cells in vivo – will help to expand the understanding of β-cell physiological functions in healthy and diseased states.